2014
DOI: 10.1038/nature13494
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution structure of the human GPR40 receptor bound to allosteric agonist TAK-875

Abstract: Human GPR40 receptor (hGPR40), also known as free fatty-acid receptor 1 (FFAR1), is a G-protein-coupled receptor that binds long-chain free fatty acids to enhance glucose-dependent insulin secretion. Novel treatments for type-2 diabetes mellitus are therefore possible by targeting hGPR40 with partial or full agonists. TAK-875, or fasiglifam, is an orally available, potent and selective partial agonist of hGPR40 receptor, which reached phase III clinical trials for the potential treatment of type-2 diabetes mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
295
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(330 citation statements)
references
References 40 publications
15
295
1
1
Order By: Relevance
“…In 2014 a X-ray crystallographic structure of the human FFA1 in complex with the ago-allosteric ligand, TAK-875 provided unprecedented three-dimensional insight into molecular recognition at FFA1 (Srivastava et al 2014). The crystal structure revealed that TAK-875 binds to the site involving transmembrane helices 3-5 and the second extracellular loop (EL2).…”
Section: X-ray Crystallography Of Ffa1mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014 a X-ray crystallographic structure of the human FFA1 in complex with the ago-allosteric ligand, TAK-875 provided unprecedented three-dimensional insight into molecular recognition at FFA1 (Srivastava et al 2014). The crystal structure revealed that TAK-875 binds to the site involving transmembrane helices 3-5 and the second extracellular loop (EL2).…”
Section: X-ray Crystallography Of Ffa1mentioning
confidence: 99%
“…The recent breakthrough in structural biology of GPCRs enabled crystallographic structures for 27 receptors of the rhodopsin family of GPCRs, including the FFA1 receptor. A FFA1 structure is solved in the complex with the ago-allosteric ligand, TAK-875 (Srivastava et al 2014) and provides a crucial point to study ligand recognition at FFA1. However, FFA2, FFA3, GPR120 and GPR84 have not been yet crystallized.…”
Section: Introductionmentioning
confidence: 99%
“…4b, 18 The crystal structure of FFA1 in complex with 1 provided an explanation for this in showing the mesylpropoxy appendage to be protruding from the ligand binding pocket towards the lipid bilayer. 7 Thus, this seems to be an optimal linkage point for attachment of a spacer-extended fluorophore. In order to gain optimal fluorescent properties of the NBD fluorophore the compound should be attached to a primary aliphatic amine.…”
Section: Design Of Fluorescent Ffa1-tracersmentioning
confidence: 99%
“…6 The recently published crystal structure of FFA1 in complex with 1 lent further support to the concept of multiple FFA1 binding sites, revealing several potential binding sites in addition to the site of 1. 7 Most importantly from a drug development standpoint, the specific binding site an FFA1 agonist interacts with may influence the ligand's downstream signaling outcomes, 2c and thus may have clear implications for the ultimate therapeutic efficacy of any developed FFA1 agonists. How these structurally similar ligands interact with their distinct binding sites on FFA1 remains poorly understood and, therefore, there is a clear need to develop novel tools to assess ligand binding to this receptor.…”
Section: Introductionmentioning
confidence: 99%
“…23 Protein preparation, refinement and docking was performed within Schrödinger's Maestro, version 2016-1. 24 To prepare FFA1 for docking, hydrogens and missing atoms were added, alternate residue positions were defined and the hydrogen bonding network was further optimized by re-orientating hydroxyls, amides and imidazole rings (of histidine residues) using Protein Preparation Wizard.…”
Section: Protein Structure Source and Preparation For Dockingmentioning
confidence: 99%